Patrones de actividad y ocupación de mamíferos y aves terrestres en bosques secos y húmedos en la cuenca del Río Magdalena (2020)
The Magdalena River basin is a region characterized by having different types of tropical forests, which vary from the tropical humid forest to the very dry tropical forest. These ecosystems contain a great biological diversity that has been influenced by the environmental variations that are present in the inter Andinos valleys of Colombia. This work evaluates the variables that explain the differences in composition and occupation of mammals and land birds in a tropical dry forest and a tropical humid forest, in the middle and upper Magdalena river basin. Camera traps located randomly throughout these forests. The methodology was based on three pillars: [1] The identification of the community of mammals and land birds and an analysis of the biodiversity of each area. [2] The activity patterns that describe the activity throughout the day (and night) of species in these areas, to later show differences in those animals present in both areas, and [3] Occupation models that by means of environmental variables and anthropogenic, they aim to assess which of them may have an impact on the occupation of a species in the territory. We found differences in the communities of mammals and land birds present in both forests, as well as a greater diversity of species in the tropical humid forest. On the other hand, for those species present in both places, there are no changes in their activity pattern despite the environmental differences in both forests. Finally, we find that for each species, one or more variables better explain the probability of occupation, the relationship between environmental variables and anthropogenic variables being notable. This can lead to implications for conservation issues and leaves the space open to continue monitoring the activity of these groups of animals for knowledge and conservation purposes in the Magdalena River basin.